2004
DOI: 10.1590/s1516-93322004000300011
|View full text |Cite
|
Sign up to set email alerts
|

Perfil peptídico de hidrolisados enzimáticos de leite em pó desnatado

Abstract: INTRODUÇÃODesde 1940, os hidrolisados enzimáticos de proteínas vêm sendo utilizados com finalidades terapêuticas para a recuperação ou a manutenção do estado nutricional de pacientes com restrições protéicas ou de aminoácidos em sua dieta. Desta forma, estas preparações enzimáticas têm sido utilizadas, tanto como suplemento em dietas para idosos e desportistas, como na fabricação de alimentos especiais para recém-nascidos prematuros, crianças com diarréia, gastroenterites, síndromes de má-absorção, fenilcetonú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
3
0
3
Order By: Relevance
“…The study of pH influence on peptide profile of casein hydrolysates, always working in the optimum pH range of the enzyme, was previously carried out by our group. It was shown that, using subtilisin, the profile produced in pH 7.5 was nutritionally superior to that in pH 8.0, giving rise to a higher di‐ and tripeptide content and lower amount of large peptides and free amino acids 37. In case of using pepsin, pH 1.9 was more advantageous than pH 2.5, producing higher small peptide content and lower quantity of large peptides 48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of pH influence on peptide profile of casein hydrolysates, always working in the optimum pH range of the enzyme, was previously carried out by our group. It was shown that, using subtilisin, the profile produced in pH 7.5 was nutritionally superior to that in pH 8.0, giving rise to a higher di‐ and tripeptide content and lower amount of large peptides and free amino acids 37. In case of using pepsin, pH 1.9 was more advantageous than pH 2.5, producing higher small peptide content and lower quantity of large peptides 48…”
Section: Resultsmentioning
confidence: 99%
“…The derivative spectrophotometry has been used in some works with varied goals, including the quantification of proteins29, 30 and the study of native and denaturated proteins 31. Also, our group has used this technique with different purposes, such as the characterization of protein hydrolysates,32 the evaluation of the exposition extent of aromatic amino acids during protein hydrolysis33–35 and the adjustment of the optimal conditions for removing phenylalanine from protein hydrolysates 36, 37. According to these authors, this technique may present some advantages over other more traditional ones related to its simplicity, quickness and relative low cost.…”
Section: Introductionmentioning
confidence: 99%
“…A seleção das variáveis e de seus níveis foi feita de acordo com a literatura (Carreira et al, 2003;Soares et al, 2004;Guo et al, 2009;Rossini et al, 2009). A análise estatística foi realizada com o auxílio do programa Statistica 8.0 (StatSoft, 2008).…”
Section: Methodsunclassified
“…Soares et al (2004) relataram que os hidrolisados proteicos de melhor qualidade devem apresentar elevados teores de dipeptídeos e tripeptídeos, assim como de peptídeos com massa molar média de 500 Da. Além disso, devem conter baixos teores de aminoácidos livres e de peptídeos com massa molar superior a 800 Da.…”
Section: Hidrolisadounclassified
“…Portanto, o hidrolisado que mais se aproxima das quantidades de aminoácidos recomendados pela FAO (1985) é o obtido pela hidrólise com a Papaína. Soares et al (2004) utilizaram três enzimas isoladamente (uma protease do Aspergillus oryzae, a Papaína e a Pepsina) para a hidrólise de leite em pó desnatado e avaliaram a ação enzimática sobre o perfil peptídico dos hidrolisados e concluíram que o melhor perfil peptídico nutricional foi obtido com a Papaína. Morais et al (2002) descreveram a influência da relação E:S sobre a hidrólise da caseína bovina com uso de papaína, e ressaltaram que a alteração da relação E:S de 2% para 4% alterou significativamente o conteúdo de todas as frações cromatográficas, e produziu um perfil peptídico distinto, com diminuição dos níveis de di-e tripeptídeos e aumento do teor de aminoácidos livres e de peptídeos médios.…”
Section: Aminoácidos Dos Hidrolisados Proteicosunclassified